Virtual Reality in Vocational Education and Training: Challenges and Possibilities - R. Ravichandran Ravichandran; Jayashree Mahapatra (Journal of Digital Learning and Education, 2023)
This article explores the challenges and possibilities in use of virtual reality (VR) as a pedagogical tool in vocational education at school level. VR has the potential to transform vocational education by providing immersive, interactive, and realistic simulations of real-world work environments to the students. The article discusses the advantages of using VR in vocational education, including increased engagement, motivation, and knowledge retention of the students. It also provides the case studies on successful integration of VR in vocational education and training. It also examines the challenges of implementing VR in vocational education, such as the cost of equipment and software, and the need for specialized technical support. The article concludes with a discussion of future directions for research on the use of VR in vocational education and the potential impact on the future of work.